Laparoscopically Harvested Omental Flap for Immediate Total Breast Reconstruction; Lessons Learnt Through Ten-Year Experience in a Tertiary Oncology Center. (April 2023) - Kahter, Ashraf; Ghazy, Hosam; Setit, Ahmed; Shams, Nazem; Gohar, Omnia; Abdelwahab, Khaled; Eldamshety, Osama; Fathi, Adel
Background. Most of the publications about Laparoscopically harvested omental flap after skin sparing mastectomy were case reports or case series. Most of them were designed for partial breast reconstruction and were lacking long-term follow-up for cosmetic results, oncologic safety, and detailed methodology. Our study aimed at highlighting the place of this method of reconstruction with long-term oncologic safety and cosmetic outcome. Methods. This study included 95 women who were candidates for skin-sparing mastectomy. Those with body mass index below 25 and above 40, those with omental resection or expected marked adhesions were excluded. All patients were consented to then undergo breast reconstruction using pedicled laparoscopically harvested omental flap. Results. The mean BMI was 34. The mean tumor size was 3.4 cm. The mean total operative time was 129 minutes. Inadequate volume occurred in 12 patients (13%). The mean total drainage output was 750 ml with 8.7% incidence of seroma. Partial breast envelop necrosis was encountered in 5 cases. Partial flap loss occurred in 2 patients. Fat necrosis occurred in 11 cases. Mastectomy and abdominal complications were accepted. Local recurrence was met in one patient and distant metastases occurred in 3 cases. 83.7% of patients expressed excellent and good aesthetic outcomes. Conclusion. When skin sparing mastectomy is chosen with suitable body mass index, laparoscopically harvested omental flap is a very safe and attractive option for total breast reconstruction with a minimal donor site morbidity, satisfactory cosmetic outcome with no compromise of the oncologic safety.